PENGARUH FAKTOR LINGKUNGAN TERHADAP KEBERADAAN GASTROPODA PADA EKOSISTEM MANGROVE DI DERMAGA LANTAMAL KELURAHAN KARANG INDAH DISTRIK MERAUKE KABUPATEN MERAUKE - Rosiana Sari Mathius; Bonny Lantang; Modesta R. Maturbongs (Musamus Fisheries and Marine Journal, 2018)
This study aims to determine the type and effect of environmental factors on the presence of gastropods in the mangrove ecosystem. Field data collection is taken by measuring the environmental parameters directly, while gastropod data is obtained by calculating directly the amount obtained by each data collection. The results showed that in Lantamal Pier there were 8 species of gastropods : Littorina scabra, Cerithidea obtusa, Cassidula angulifera, Terebralia sulcata, Terebralia palustris, Ellobium aurisjudae, Telescopium-telescopium and Nerita lineata while environmental factors that affected to gastropods were water temperature, water pH, and soil pH. Keywords: Gastropods; Environmental parameters.